Peran Hukum Perjanjian Dalam Aktivitas Bisnis “The Role Of Agreement Law In Business Activities” - Eliza Oktaliana Sari (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
The correlation between law and economics is so close and mutuallyinfluencing, to meet various human needs in their social life. Economicdevelopment will affect the implementation of the law. Likewise incarrying out various business activities, the role of the legal sector isvery important, especially to facilitate business development both on anational and international scale. This can be realized through themaking of an agreement by the business actors. Agreement as a private legal relationship that exists between parties who have entered into an agreement, on the object that has been agreed upon as a form of fulfilment of rights and obligations, after the agreement is created. This refers to the source of contract law, taking into account the legal terms of the agreement, the principles of contract law, and the stages of making the agreement, so that it can run effectively and efficiently. To support the writing of this journal, the author uses the library research method, which examines a number of scientific books, journals, theories and concepts that discuss contracts and various business activities.